2022
DOI: 10.3389/fimmu.2022.1012078
|View full text |Cite
|
Sign up to set email alerts
|

Acid external and internal environment exchange the Oreochromis niloticus tissue immune gene expression compared to the mouse macrophage polarization model

Abstract: The water environment plays an important role in animal physiology. In this study, we sought to evaluate the effect of the acid environment on the Oreochromis niloticus (Nile tilapia) internal microenvironment immune response compare to the mouse macrophage model (J77A.1). The acid environment treated mouse macrophage J774A.1 model have shown that acidic treatment is able to polarize macrophages into M2-like macrophages via an increase in Ym1, Tgm2, Arg1, Fizz1, and IL-10 expression. Metabolic analysis of mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…ABCF1 also regulates other innate immune functions. Previous studies have shown that a cell counteracts dsRNA infection via Oas1-RNase L mediated viral degradation [28][29][30]. Our studies also suggest that ABCF1 regulates this signaling pathway by interacting with OAS1a and controlling its 2'5'A activity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…ABCF1 also regulates other innate immune functions. Previous studies have shown that a cell counteracts dsRNA infection via Oas1-RNase L mediated viral degradation [28][29][30]. Our studies also suggest that ABCF1 regulates this signaling pathway by interacting with OAS1a and controlling its 2'5'A activity.…”
Section: Discussionsupporting
confidence: 70%
“…Together with ABCF1 siRNA knockdown, the assay was used to measure either enhance or inhibit phagocytosis. The assay was performed as described by the [31].…”
Section: Methodsmentioning
confidence: 99%